2005
DOI: 10.1111/j.1346-8138.2005.tb00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Lobular Capillary Hemangioma: Two Case Reports

Abstract: Lobular capillary hemangioma, also known as pyogenic granuloma, is a common, solitary, benign neoplasm of the skin and mucous membranes. The etiology of this lesion remains unknown. Lobular capillary hemangioma can present rarely in a disseminated form, usually associated with other disorders. Two patients, aged 17 and 33, were admitted to the dermatology clinic with disseminated lobular capillary hemangiomas which appeared suddenly. There was no history of trauma in either case. The histopathology of the lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Histological studies revealed prominent capillary dilatation without hobnail endothelial cells, which is exclusively present in EPA [8] . Distinction from disseminated pyogenic granulomas is easy as angiomatous tissue tends to occur in discrete masses, surrounded by myxoid stroma containing scattered spindle-and stellate-shaped connective tissue cells [9] . The main distinguishing feature of eruptive cherry angioma is that the domeshaped papules are composed of numerous newly formed capillaries with narrow lumina and prominent endothelial cells arranged in a lobular fashion in the subpapillary region [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies revealed prominent capillary dilatation without hobnail endothelial cells, which is exclusively present in EPA [8] . Distinction from disseminated pyogenic granulomas is easy as angiomatous tissue tends to occur in discrete masses, surrounded by myxoid stroma containing scattered spindle-and stellate-shaped connective tissue cells [9] . The main distinguishing feature of eruptive cherry angioma is that the domeshaped papules are composed of numerous newly formed capillaries with narrow lumina and prominent endothelial cells arranged in a lobular fashion in the subpapillary region [10] .…”
Section: Discussionmentioning
confidence: 99%